Pelatihan Jurnalisme Hijau: Menulis, Menginspirasi dan Menjaga Lingkungan - Dwi Firmansyah; Rika Jessica Rahma; Aditya Rizky Gunanto (Education and Talent Development Center of Indonesia, 2025)
The escalating environmental crisis demands urgent involvement from young generations who will inherit the consequences of climate change. Schools play a strategic role in building ecological awareness, yet environmental education often remains theoretical and detached from students’ daily lives. In response, this community engagement programme was designed to empower high school students with basic skills in environmental journalism, or green journalism, as a medium to communicate ecological issues in an engaging and responsible way. The programme was implemented on 24 February 2025 at SMA Negeri 2 Tangerang Selatan with 80 participants consisting of students and teacher mentors. Using a humanist and participatory approach, the training combined theory and practice: after learning the 5W1H news structure, students directly produced news leads based on environmental photos; small-group mentoring supported confidence building; and social media was utilised to create educational campaigns. Participants were divided into three parallel classes, each with approximately 27 members, guided by lecturers of the Faculty of Communication Sciences, Universitas Mercu Buana. The results indicate significant improvements in students’ journalistic competence and ecological literacy. Post-test results revealed that 85% of participants demonstrated progress in news writing and fact-checking. Beyond technical enhancement, students began to see themselves as ecological storytellers and agents of change. The school also committed to establishing a Green Journalism Club as a sustainable platform for student initiatives. In conclusion, this training underscores that green journalism can serve as both an educational strategy and a participatory avenue for environmental action, enabling students and schools to collectively confront ecological challenges through creative and responsible communication.